THE INFLUENCE OF INTERNAL CONTROL SYSTEM AND SERVICE QUALITY ON GOOD UNIVERSITY GOVERNANCE, MODERATED BY ORGANIZATION CULTURE - Novi Faurini; M. Irsan Nasution; Renny Maisyarah (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to examine the extent to which the Internal Control System (ICS) and Service Quality influence the implementation of Good University Governance (GUG), with Organizational Culture acting as a variable that strengthens these relationships at LP3I Banda Aceh. The research employed a quantitative approach through the distribution of questionnaires to lecturers and staff. The processed data, analyzed through multiple linear and moderated regression approaches (MRA), indicate that strengthening the Internal Control System (ICS) contributes positively and significantly to improving the implementation of Good University Governance (GUG), whereas Service Quality shows no significant impact. Organizational Culture also exerts a positive influence on GUG but does not moderate the relationships between the Internal Control System or Service Quality and GUG. These results emphasize that reinforcing internal control mechanisms and fostering a healthy organizational culture are key factors in achieving accountable and transparent university governance. Meanwhile, service quality plays a greater role in enhancing stakeholder satisfaction rather than directly influencing governance practices. This study contributes to higher education management by highlighting the importance of strengthening internal control effectiveness and cultivating organizational culture as fundamental pillars in building governance systems that uphold accountability, transparency, and sustainability